Feeding strategies for the acquisition of high‐quality food sources in stream macroinvertebrates: Collecting, integrating, and mixed feeding. (6th May 2018) - Guo, Fen; Bunn, Stuart E.; Brett, Michael T.; Fry, Brian; Hager, Hannes; Ouyang, Xiaoguang; Kainz, Martin J.
Abstract: Aquatic macroinvertebrates play an important functional role in energy transfer in food webs, linking basal food sources to upper trophic levels that include fish, birds, and humans. However, the trophic coupling of nutritional quality between macroinvertebrates and their food sources is still poorly understood. We conducted a field study in subalpine streams in Austria to investigate how the nutritional quality (measured by long‐chain polyunsaturated fatty acids, LC‐PUFAs) in macroinvertebrates changes relative to their basal food sources. Samples of macroinvertebrates, periphyton, and leaves were collected from 17 streams in July and October 2016 and their fatty acid (FA) composition was analyzed. Periphyton FA varied strongly with time and space, and their trophic effect on macroinvertebrate FA differed among functional feeding groups. The match between periphyton FA and macroinvertebrate FA decreased with increasing trophic levels, but LC‐PUFA content increased with each trophic step from periphyton to grazers and finally predators. Macroinvertebrates fed selectively on, assimilated, and/or actively controlled their LC‐PUFA, especially eicosapentaenoic acid (EPA, 20 : 5ω3) relative to their basal food sources in the face of spatial and temporal changes. Grazer FA profiles reflected periphyton FA with relatively good fidelity, and especially their EPA feeding strategy was primarily linked to periphyton FA variation across seasons. In contrast, shredders appeared to preferentially assimilate more EPA over other FA, which was determined by the availability of high‐quality food over seasons. Predators may more actively control their LC‐PUFA distribution with respect to different quality foods and showed less fidelity to the basal FA profiles in plants and prey. Overall, grazers and shredders showed relatively good fidelity to food FA profiles and performed as both "collectors" and "integrators" for LC‐PUFA requirements across seasons, while predators at higher trophic levels were more "integrators" with added metabolic complexity leading to somewhat more divergent FA profiles. These results are potentially applicable for other aquatic consumers in freshwater and marine ecosystems.